Pengembangan Sistem Perencanaan Pendidikan Islam Berbasis Kebutuhan dan Karakteristik Peserta Didik - Habibah Habibah; Ahmad Salabi; Yahya MOF (MAN 4 Kota Pekanbaru, 2026)
This study discusses the development of an Islamic education planning system based on the needs and characteristics of learners through a literature review approach. Educational planning in Islamic institutions often focuses more on administrative aspects than on understanding students’ diverse potentials, interests, and learning styles. This research aims to analyze strategies for developing adaptive educational planning in Islamic education. The study uses a literature review method by examining journals, books, and relevant academic sources. The results show that effective educational planning requires learner needs analysis, curriculum flexibility, data-based planning, integration of Islamic values, and continuous evaluation. Such a system contributes to improving learning effectiveness, student participation, and holistic educational outcomes.